ELAZIĞ VE MALATYA'DA ÇIRAKLIK EĞİTİMİ VE SORUNLARI - TAŞPINAR, MEHMET (Fırat Üniveristesi, 1992)
Vocational education »sa process which gives a person knowledge and skill on various levels. The scientific and technological developments create qualified professions and manpower which are needed day by^day. Different vocational education approaches have been carried out to train qualified manpower on different levels. One of them is apprenticeship training. The purpose of apprenticeship training is to train qualified master and assistant master. The purpose of this research ist© determine the problems of apprenticeship training in Malatya and Elazığ and develop solutions by taking national problems into consideration, so the outputs were optained by using questionnaire method from three groups. These groups were formed from 156 masters. 264 apprentice students and 27 vocational teachers. According to outputs, these are the main problems: The payments that the students take are insufficient. Their work days are illegal and they work on vacations. Generally their working places are not heafl% and safe to work. Students canned :. take the benefits of knowledge which they learned at school (Apprenticeship Training Centre). The time of training which is one day in a week is inadequate. As the goverment does not pay their insurance premiums in the assistant mastership period, the interest towards apprenticeship training decreases. At the assistant mastership and mastership exams the occupational competences are not taken into
Keywords: Eğitim ve Öğretim; Education and Training